Poetic Images of (Karim Dashti´s) Poems - Kamaran Aba-Bakr Khudhur Khoshnaw (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The poetic image is a basic artistic genre which is present in every poem and is born at every stage. Therefore, if we read any poetic text carefully, we will feel many various poetic images, which directly express: The poet’s thoughts and worldview for life. Expressing feelings towards self, God and the phenomena. It is the reflection of dreams, imagination, passions and wishes. Poetic image is narration, depicting, imagining of life experience. It is the most active element of poetry, so it has become a must of any poetic text. Karim Dashi’s poems are full of poetic images, because of his poetic images. On one hand, he has been able to attract the reader’s attention and enjoyment, and on the other hand he makes the reader think in a way that the reader has become the centre of text analysis.